2003
DOI: 10.1530/eje.0.1490039
|View full text |Cite
|
Sign up to set email alerts
|

Increased plasma concentrations of osteoprotegerin in type 2 diabetic patients with microvascular complications

Abstract: Objective: Osteoprotegerin (OPG) is a newly identified inhibitor of bone resorption. Recent studies indicate that OPG also acts as an important regulatory molecule in the vasculature. Plasma levels of OPG seem to be elevated in subjects with diabetes as well as in non-diabetic subjects with cardiovascular disease. The aim of the present study was to examine the association between plasma OPG levels and microvascular complications and glycemic control in patients with type 2 diabetes. Design and methods: Four g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
125
0
6

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(148 citation statements)
references
References 12 publications
16
125
0
6
Order By: Relevance
“…This was first shown by Browner et al [12], who reported that although no associations were seen between the bone parameters and plasma osteoprotegerin levels, individuals with diabetes as well as persons with cardiovascular disease had increased values. Since then, these findings have been confirmed in both type 1 [38,39] and type 2 diabetes [13,40]. Moreover, we recently found that plasma osteoprotegerin is increased in subgroups of type 1 diabetic patients with nephropathy and in subgroups with signs of cardiovascular disease [18].…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…This was first shown by Browner et al [12], who reported that although no associations were seen between the bone parameters and plasma osteoprotegerin levels, individuals with diabetes as well as persons with cardiovascular disease had increased values. Since then, these findings have been confirmed in both type 1 [38,39] and type 2 diabetes [13,40]. Moreover, we recently found that plasma osteoprotegerin is increased in subgroups of type 1 diabetic patients with nephropathy and in subgroups with signs of cardiovascular disease [18].…”
Section: Discussionmentioning
confidence: 56%
“…Cardiovascular disease was considered present at baseline in patients with a history of admission for stroke or myocardial infarction. Plasma osteoprotegerin was measured by a sandwich ELISA using commercially available antibodies (R&D Systems, Minneapolis, MN, USA), as previously described [13]. Briefly, mouse antihuman osteoprotegerin (R&D Systems) was used as capture antibody and a biotinylated goat anti-human osteoprotegerin (R&D Systems) for detection.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Browner and colleagues found that serum OPG concentrations were higher in women with diabetes and that they correlated with cardiovascular risk [28]. Serum concentrations of OPG were also found to be higher in another small study of patients with Type 2 diabetes, and possibly associated specifically with microvascular complications [29]. There is evidence that the OPG/RANK-L system is involved in the accelerated vascular calcification of chronic renal failure [30], and it has been shown that it is modulated in vitro by inorganic phosphate [31].…”
Section: Rank-l and Opg In Human Diseasementioning
confidence: 95%